PROHIBITION OF HATE SPEECH IN THE QUR'AN AND ITS RELATIONSHIP WITH THE RELIGIOUS MODERATION - Reza, Muhammad Dzaky (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
This article aims to explore the concept of hate speech in the Qur'an, its narrative form, and the Qur'an's response to hate speech behavior. The object is al-Qur'an Surah al-An'am [6] verse 108, which contains the narrative of hate speech. Using qualitative methods and content analysis, this article concludes that in Surah Al-An'am [6] verse 108, there is a prohibition on hate speech, namely the banning of insulting followers of other religions. This form of humiliation can take the form of insulting places of worship and religious symbols and even forcibly disbanding religious events. Besides that, in Surah al-An'am [6] verse 108, also teaches about religious moderation by inviting Muslims to have tolerance in religion and respect for followers of other religions by not insulting or disturbing them according to what is said in the text of the Qur'anic verse. It is hoped that this research can be one of the efforts to support religious moderation programs in Indonesia so that Muslims can provide peace for all religious people and show the face of Islam, Rahmatan Lil 'alamīn.